PERAN ARTIFICIAL INTELLIGENCE DALAM OPTIMALISASI PEMUNGUTAN PAJAK BARANG DAN JASA TERTENTU - Amelia Puteri Nurchoiriyah; Emeliatus Sofia; Mohamad Djasuli; Fitriyah Fitriyah; Khairul Amala (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the role of artificial intelligence (AI) in the optimization of tax collection on certain goods and services, with a focus on improving accuracy and administrative efficiency and reducing the tax gap. Methods: Through the literature review method, this study identifies that AI is capable of transforming the tax system through predictive analytics, transaction anomaly detection, and reporting automation, as evident in the implementation in countries such as Estonia and Singapore. However, implementation challenges in Indonesia include limited digital infrastructure, regulatory gaps, and human resource resistance. Results: The research findings recommend a holistic approach that combines infrastructure strengthening, specific legal frameworks, and human resource training to maximize the potential of AI in an inclusive and equitable manner. Keywords: Artificial intelligence, tax optimization, tax gap.